The Spodoptera frugiperda L-aminoacylase degrades fatty acid-amino acid conjugates and promotes larvae growth on Zea mays - Bin Li; Mei Luo; Xiaofeng Liu; Wangpeng Shi; Jinfeng Qi; Shaoqun Zhou; Guirong Wang (Communications Biology)
Abstract Oral secretions (OS) contain diverse functional molecules that play important roles in the molecular interactions between insect herbivores and their host plants. Components of OS have been hypothesized to facilitate adaptation of specialized herbivores towards their preferred hosts. In this study, we identified an L-aminoacylase-encoding gene, SfruACY, that was preferentially up-regulated in the salivary glands of Spodoptera frugiderpa larvae when feeding on maize leaves compared to artificial diet. The protein product was confirmed to catalyze the in vitro degradation of fatty acid-amino acid conjugates (FACs), the classic plant defense elicitors commonly found in the OS of lepidopteran caterpillars. Generation of a homozygous SfruACY knock-out line with the CRISPR-Cas9 technology further revealed that the activity of this gene could promote the growth of S. frugiperda larvae on maize leaves but was not required for larvae growth on artificial diet. Finally, comparative transcriptomic analyses of maize leaves showed more pronounced inducible defense responses when attacked by the SfruACY knocked-out larvae than the wildtype intruders. These experimental evidences support that the inducible expression of SfruACY by maize leaf diet in the salivary glands of S. frugiperda larvae can lower the FAC contents in their OS, and hence facilitate larvae growth likely by inducing weaker plant defense responses. Our findings provide a mechanistic explanation for a longstanding observation that S. frugiperda larvae induce weaker plant defense responses, and shed light on transcriptional regulation as a potential mean for insect herbivores to adapt towards their preferred host plant species.